👤

Rezolvati prin metoda substitutiei si prin metoda reducerii:[tex] \left \{ {{x( \sqrt{2}+1)+y= \sqrt{2} }\atop {x+( \sqrt{2}-1)y=1 } \right. [/tex]

Răspuns :

x(√2+1)+y=√2
x+(√2-1)y=1 inmultim cu √2+1

x(√2+1)+y=√2
x(√2+1)+(√2-1)(√2+1)y=√2+1

x(√2+1)+y=√2
x(√2+1)+y=√2+1
le scadem membru cu membru 
0= -1 nu are solutii..

varianta cu -
x(√2+1)+y=√2
x-(√2-1)y=1     inmultim cu √2+1

x(√2+1)+y=√2
x(√2+1)-(√2-1)(√2+1)y=√2+1

x(√2+1)+y=√2
x(√2+1)-y=√2+1
le scadem membru cu membru 
2y=-1
y=-1
x(√2+1)+1=√2+1
x(√2+1)=√2
x=√2/(√2+1)=1+√2